MR imaging of protein folding in vitro employing Nuclear-Overhauser-mediated saturation transfer - Zaiss, Moritz; Radbruch, Alexander; Bachert, Peter (NMR in biomedicine, 2013)
MR Z-spectroscopy allows enhanced imaging contrast on the basis of saturation transfer between the proton pools of cellular compounds and water, occurring via chemical exchange (chemical exchange saturation transfer, CEST) or dipole-dipole coupling (nuclear Overhauser effect, NOE). In previous studies, signals observed in the aliphatic proton region of Z-spectra have been assigned to NOEs between protons in water molecules and protons at the surface of proteins. We investigated a possible relationship between the signal strength of NOE peaks in Z-spectra obtained at B0 = 7 T and protein structure. Here, we report a correlation of NOE-mediated saturation transfer with the structural state of bovine serum albumin (BSA), which was monitored by fluorescence spectroscopy. Encouraged by CEST signal changes observed in tumor tissue, our observation also points to a possible contrast mechanism for MRI sensitive to the structural integrity of proteins in cells. Therefore, protein folding should be considered as an additional property affecting saturation transfer between water and proteins, in combination with the microenvironment and physiological quantities, such as metabolite concentration, temperature and pH. Copyright © 2013 John Wiley & Sons, Ltd.